Cranial cruciate ligament rupture in large and giant dogs - Guénégo, L.; Zahra, A.; Madelénat, A.; Gautier, R.; Marcellin-Little, D. J.; Hulse, D. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Forty-two dogs weighing between 30 and 87 kg (mean body weight of 49 kg) with cranial cruciate ligament ruptures (CCLR) were treated with a modified lateral extra-capsular stabilization using braided polyester prosthetic ligament-suture anchor technique. Clinical and radiographic outcomes of 48 stifles were retrospectively evaluated with a mean follow-up of 18 months. Ten dogs had pulled out their bone anchors with no clinical relevance. Draining tracts did not appear. Despite mild radiographic progression of osteoarthritis, all of the dogs regained acceptable function of the operated limb.
Keywords: BoneBiter®; suture anchor; cranial cruciate ligament; polyester prosthetic ligament; draining track